The impact of using the device proposed in the development of performance skill to stand on hands Palmrgehh on a parallel device for men - Abdul Amir, sajad (Journal of Physical Education, 2011)
The importance of research focused on a proposal assist device proposal to develop the performance skills to stand on their hands Palmrjehp on a parallel, the importance of giving in such research belong to the parallel system, as well as skill as key to the majority of the skills of your parallel port Through For the researcher Samuel gymnastic world, videos and compare the level of technical performance of this skill in the country of Iraq found that there is a weakness in the level of technical performance in certain skills on a parallel for men with a lot of young players, particularly skill to stand on the hands and reason is not to loan the basic skill great importance Awakes for its role in mastering the many skills difficult that depend on them, prompting Scholar to take her as a problem to study and find appropriate solutions to development, which invited the researcher to the design of the Assistant proposal launched by the security sensor laser as it contributed to discover mistakes and help coach in the diagnosis and therefore contribute to training and skill in the performance of image optimization. Objective of this research: - 1 - the design of the Assistant proposal to develop the performance skills to stand on their hands Palmrjehp on a parallel (for men) with the young players. Hypothesizes: - 1 - Assistant of the device proposed a positive impact in the development of performance skills to stand on their hands on a parallel (for men) to the young players. Research fields: - Area HIV / sample of (5) players from the emerging Army Sports Club and ages (10-12) years.